Strategic Public Relations for Digital Sovereignty and Environmental, Social, and Governance Integration in the Telecommunications Industry - Fani Lutfiyatun Nisa; Widya Fatimatuz Zahra; Gita Rahmawati; Pramudya Ibnu Subrata (The Indonesian Institute of Science and Technology Research, 2026)
This study explores the strategic role of public relations (PR) within PT Telkom Indonesia (Persero) Tbk, conceptualizing it as an integral management function that drives market value and corporate resilience. Amidst the rapid digitalization and geopolitical uncertainties of 2025–2026, the research investigates how PR manages the intersection of digital sovereignty, Environmental, Social, and Governance (ESG) integration, and market authority. Utilizing a conceptual research approach through a systematic literature review, this study synthesizes Excellence Theory and Stakeholder Theory to develop an Integrated PR-Management (IPM) model. The findings demonstrate that PR at Telkom acts as a strategic architect by transforming technical infrastructure initiatives such as the launch of the Satelit Merah Putih 2 and decarbonization efforts into authoritative narratives that enhance investor trust and secure regulatory legitimacy. Furthermore, the study highlights that effective PR communication, validated by external accolades like the PR Indonesia Awards, is essential for navigating B2B markets and mitigating reputational risks. The analysis emphasizes that digital reputation is a critical intangible asset, and the alignment of PR Key Performance Indicators (KPIs) with core business metrics is vital for long-term sustainability. The proposed IPM framework offers a roadmap for state-owned enterprises to navigate technological disruptions by bridging technical operational excellence with persuasive strategic communication. Consequently, this research underscores the necessity of reforming traditional siloed communication structures into AI-integrated, fluid units to maintain competitiveness in the 2026 digital era.